IVR-UNED: Interactive virtual environments to understand radiation fields - Mario Belotti; Rafael Juárez (Nuclear Engineering and Technology)
As a result of the evolution of High-Performance Computing (HPC) and new cutting-edge projects such as ITER, nuclear analysis has greatly increased in sophistication. Nowadays, nuclear facilities can be modelled in unprecedented detail for radiation transport calculations. Radiation maps can reach great levels of complexity, including multiple radiation sources in vast geometries. These capabilities must be accompanied by an equal capacity to process the results obtained. Nowadays clients are provided with static views pre-decided by nuclear analysts to understand radiation fields. Since the ability to understand such information depends on the unevenly distributed spatial intelligence, this practice can induce biases and limit the usability of the calculations. But beyond analyst-client communication, analysts themselves often fail to identify cleanly all the aspects of a complex radiation field. To overcome to these limitations, we have expanded the videogame engine Unity to create IVR-UNED. It permits to build 3D videogame-like interactive virtual immersive environments, boosting the visualization and insight of the radiation fields through easy on-demand and real-time radiation field postprocessing and visualization. To demonstrate its features, the application to two relevant examples for fusion-related facilities, ITER and IFMIF-DONES, will be presented.